2022
DOI: 10.1093/cvr/cvac096
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial brain-derived neurotrophic factor regulates cardiac bioenergetics through the transcription factor Yin Yang 1

Abstract: Aims Brain-derived Neurotrophic Factor (BDNF) is markedly decreased in heart failure patients. Both BDNF and its receptor, Tropomyosin Related Kinase Receptor (TrkB), are expressed in cardiomyocytes, however the role of myocardial BDNF signaling in cardiac pathophysiology is poorly understood. Here we investigated the role of BDNF/TrkB signaling in cardiac stress response to exercise and pathological stress. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…32 Moreover, we recently showed that BDNF regulates cardiac bioenergetics by modulating the expression of the transcription factor Yin Yang1. 33 With overt HF, as in the case of chronic LV dysfunction occurring 4 weeks after infarcted in mice, 20 the initial compensatory sympathetic overdrive 34,35 becomes maladaptive, altering βARs sensitivity/coupling to G proteins, ultimately lowering cardiac contractility/inotropic reserve. 35 Among other signatures of adrenergic dysregulation, there is a substantial loss of β1AR density (≅50%) at the plasma membrane level and a marked dysfunction of β3AR, too.…”
Section: Bdnf and βAr Signaling In Chfmentioning
confidence: 99%
“…32 Moreover, we recently showed that BDNF regulates cardiac bioenergetics by modulating the expression of the transcription factor Yin Yang1. 33 With overt HF, as in the case of chronic LV dysfunction occurring 4 weeks after infarcted in mice, 20 the initial compensatory sympathetic overdrive 34,35 becomes maladaptive, altering βARs sensitivity/coupling to G proteins, ultimately lowering cardiac contractility/inotropic reserve. 35 Among other signatures of adrenergic dysregulation, there is a substantial loss of β1AR density (≅50%) at the plasma membrane level and a marked dysfunction of β3AR, too.…”
Section: Bdnf and βAr Signaling In Chfmentioning
confidence: 99%
“…TAC procedure was performed as previously described (Yang et al, 2022). Briefly, sterile surgery was performed in our dedicated facility.…”
Section: Star✶methodsmentioning
confidence: 99%
“…The chest was then closed with a 6-0 proline suture and 5-0 silk suture. Serial echocardiography was performed in sedated mice (TAC) and conscious mice (12-months-old) as described previously (Yang et al, 2022).…”
Section: Star✶methodsmentioning
confidence: 99%
“…As previously described, 44 hearts from 1–2-day old Sprague Dawley rat pups were excised into cold buffer (NaCl 137mM, KC1 5.36mM, MgSO4– 7H2O 0.81mM, dextrose 5.55mM, KH2PO4 0.44mM, Na2HPO4–7H2O 0.34mM, and HEPES 20mM at pH 7.5). Ventricles were cleared of blood and dissected into 1–2mm pieces to digest out cardiomyocytes using multiple incubations in trypsin (0.04%) and collagenase (0.4mg/ml) at 37°C on a rocking platform.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were cultured in serum free DMEM containing 0.1% Insulin-transferrin-selenium (Thermo Fisher Scientific). 44…”
Section: Methodsmentioning
confidence: 99%